Analisis Sosiokultural Penundaan Pernikahan pada Wanita Karir: Studi Kasus Kota Depok - Raihana, Siti Nazla; Abdullah, Hasna' Mumtaza (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study explores the postponement of marriage among career women in Depok City in the context of dynamic urban life. Using a qualitative approach through case studies, 10 informants from diverse backgrounds were purposefully selected. The results show that marriage postponement is influenced by career considerations, fears of career setbacks, and financial and emotional unpreparedness. The negative impacts of delaying marriage include social pressure, feelings of insecurity, loneliness, and increased workplace engagement. The positive impacts include greater marriage preparation, a focus on career development, good time management, and personal growth. This study emphasizes the importance of understanding the various factors that influence the decision to delay marriage and its impact on the lives of career women in Depok City. The findings provide insights for policymakers, researchers, and individuals navigating their careers and personal lives.